Municipal service delivery: the role of transaction costs in the choice between alternative governance mechanisms - Rodrigues, Miguel (2012)
Service provision by local governments can be delivered using in-house bureaucracies, private firms, and partnerships with other governments or the not-for-profit sector. This production decision has been a major focus of discussion among scholars, practitioners and political agents for the last quarter of a century. The transaction costs framework is an important tool to analyse decisions regarding the production of local services. In this paper, the authors employ this framework to analyse service delivery in Portugal and find that service characteristics and the local political environment play a key role in local officials’ choice among the three governance mechanisms to deliver public services